PDA

View Full Version : linear equations/elimination

babeegirl
11-19-2009, 08:18 PM
help. im 13 and have a test on linear equations/elimination. i need help simplifying.....
5x-2y=-15
2x-2y=-12

this is how far i got
2(5x-2y=-15)
10x-4y=-30

Subhotosh Khan
11-19-2009, 09:44 PM
help. im 13 and have a test on linear equations/elimination. i need help simplifying.....
5x-2y=-15.............................................(1)
2x-2y=-12.............................................(2)

this is how far i got
2(5x-2y=-15)
10x-4y=-30.............................................(3)

Now multiply the equation (2) by 5

5(2x-2y) = 5*(-12)

10x - 10y = -60........................................(4)

Now we subtract (4) from (3) - what do we get?

[spoiler=:3rvogiay]10x - 4y - (10x - 10y) = -30 - (-60)

-4y + 10y = 30[/spoiler:3rvogiay]

Continue.......

babeegirl
11-19-2009, 10:45 PM
[quote="Subhotosh Khan"][quote="babeegirl"]help. im 13 and have a test on linear equations/elimination. i need help simplifying.....
5x-2y=-15.............................................(1)
2x-2y=-12.............................................(2)

this is how far i got
2(5x-2y=-15)
10x-4y=-30.............................................(3)

Now multiply the equation (2) by 5

5(2x-2y) = 5*(-12)

10x - 10y = -60........................................(4)

Now we subtract (4) from (3) - what do we get?

10x - 4y - (10x - 10y) = -30 - (-60)

-4y + 10y = 30

then......
10x-4y=6?

Mrspi
11-19-2009, 11:02 PM
help. im 13 and have a test on linear equations/elimination. i need help simplifying.....
5x-2y=-15
2x-2y=-12

this is how far i got
2(5x-2y=-15)
10x-4y=-30

A good RULE OF THUMB is to look at the equations, and determine what would be the EASIEST way to eliminate one of the variables.

I notice that the y-terms are both -2y...if ONE of the equations had +2y instead of -2y, the y terms would add up to 0, right?

Let's multiply one of the equations by -1. Makes no difference which you do that to...so I'll multiply both sides of the first equation by -1:

-1(5x - 2y) = (-1)(-15)
-5x + 2y = 15
This is our "new and improved" version of the first equation.

Ok...now we have THIS system:
-5x + 2y = 15
2x - 2y = -12